NAVY WOMEN SERVICE EXPERIENCE (1941-1945). BASED ON MATERIALS OF THE SOUTH OF RUSSIA - G. N. Kameneva (Гуманитарные и юридические исследования)
This article presents the analysis of women recruitment in Navy during the Great Patriotic War in the South Russia, the organization problems and periods of mass drafts, the work of medical commissions, the causes of women dropout, the original military training of recruits and the training of seaborne assault troopers, the service conditions of the Red Navy women ets. The tragic experience examples of first women mobilization stream during the Kerchensk retreat of Soviet troops in May 1942 are adduced. In the course of the study it is concluded that over the years more than four thousands of south Russia Komsomol women served over twenty-five specialties as part of the Black Sea and Baltic fleets and the Caspian military fleet. Despite of all the costs of operational mobilizations the replacement between men and women in different posts let release men to stay in front lines.